Secession and Separatist Conflicts in Postcolonial Africa - Falola, Toyin; Thomas, Charles G. (Africa: Missing Voices, 2020)
The first book to examine the full historical arc of secession and secessionist conflict across sub-Saharan Africa. Wars fought for political separation have become omnipresent in post-colonial Africa. From the division of Sudan, to the continued fragmentation of Somalia, and the protracted struggles of Cabinda and Azawad, conflict over secession and separation continues to the present day. This is the first single volume to examine the historical arc of secession and secessionist conflict across sub-Saharan Africa. Paying particular attention to the development of secessionist conflicts and their evolving goals, Secession and Separatist Conflicts in Postcolonial Africa draws on case studies and rigorous research to examine three waves of secessionist movements, themselves defined by international conflict and change. Using detailed case studies, the authors offer a framework to understand how secession and separation occur, how these are influenced by both preceding movements and global political trends, and how their ongoing legacies continue to shape African regional politics. Deeply engaging and thoroughly researched, this book presents a nuanced and important new overview of African separatist and secessionist conflicts. It addresses the structures, goals, and underlying influences of these movements within a broader global context to impart a rich understanding of why these conflicts are waged, and how they succeed or fail.